Peran Dakwah Dalam Era Digital Eksplorasi Potensi Media Sosial Dalam Penyebaran Nilai-Nilai Islam - Hafizhah Najmatulhasna Sofyan; Hafilia Muzniyyah; Ismail Mubarok (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
In the current digital exploration era, many young generations are very open to the times. For this reason, the younger generation needs Islamic teachings as a basis in responding to the current of modernization. The teachings of Islam can be obtained through da'wah. This research journal was created to open the eyes of the public in order to make good use of modern facilities that already exist, such as preaching on social media. Then, the method used in this study, namely qualitative descriptive method. The qualitative descriptive method is a research pattern whose type is more in-depth to describe an object, phenomenon, and one's experience through interpretive study. Da'wah in the digital era, of course, requires digital technology as a means of distribution. Islamic learning digital technology, can be accessed through digital platforms, such as online classes, webinars, or courses. As well as social media, such as tiktok, youtube, instagram etc. Da'wah spread through social media, can reach even not only generation Z, but all generations. So that the teachings of Islam can be understood or followed by the general public.